Customisation and validation of a low-volume plasma renin activity immunoassay: Enabling of regulatory compliant determination in paediatric trials - Suessenbach, F.K. (Pract Lab Med, 2019)
OBJECTIVES: Investigations of plasma renin activity (PRA) in children are urgently required. Small-volume, regulatory guideline compliant, bioanalytical assays tailored for paediatric application could facilitate to overcome this hurdle. Ethical constraints given e.g. by the European Medicines Agency need to be addressed and reliable data generation in line with Good Clinical Laboratory Practice must be ensured. METHODS: A PRA enzyme-linked immunosorbent assay (ELISA) was tailored for paediatric application and validated in the context of the U.S. Food and Drug Administration bioanalytical guideline. Performance verification of the assay was conducted by participation in an interlaboratory ring test, evaluation of incurred sample reanalysis and an application-orientated approach in children. RESULTS: A five-fold reduction of required plasma volume to 100 μL was achieved without limiting the calibration range. Between-run accuracy and precision varied no more than 5.0% and 6.3%, respectively. No substantial matrix effect was detected and the inter-run precision for parallelism was 11.1%. Stability experiments approved the freeze-thaw stability, short-term stability as well as 37 weeks of long-term stability. The assay successfully participated in the interlaboratory ring test, showing non-inferiority regarding radioimmunoassay (RIA). Moreover, PRA in plasma samples of neonates was successfully determined. Conducted incurred sample reanalysis confirmed the comparability and reliability of the assay with regard to international regulatory bioanalytical guidelines. CONCLUSION: A fit-for-purpose PRA ELISA characterised by low-volume application was successfully established, indicating non-inferiority regarding commonly applied RIAs. Reliability of the regulatory-compliant PRA assay was proven by participation in an interlaboratory ring test and its application in a paediatric population.